Ermittlung der Teilnahmebereitschaft an Vertragsnaturschutzprogrammen und der dafür notwendigen Ausgleichszahlungen mit Hilfe eines Discrete-Choice-Experimentes; Factors affecting Participation and Compensation Requirements in Agri-Environmental Schemes: Insights from a Discrete Choice Experiment - Gunnar Breustedt; Norbert Schulz; Uwe Latacz-Lohmann (German Journal of Agricultural Economics (GJAE), 2013)
– This paper uses data from a discrete choice experiment to investigate the factors affecting participation in agri-environmental schemes in Eiderstedt and Sud̈tondern, two grassland regions in Schleswig-Holstein. As expected, higher payment rates increase farmers' willingness to sign a conservation contract whereas stricter management prescriptions reduce participation. Besides contract design variables, a number of farm-specific variables affect farmers' willingness to participate. Farmers, for instance, with previous experience in agri-environmental contracting are more likely to choose a contract than those without such experience. Our estimates of marginal willingness-to-accept show that farmers regard contractual obligations relating to fertilizer use and mowing dates as particularly demanding, resulting in high compensation requirements of exteuro100 - 200 per hectare. Farms with high land use intensities - e.g. high stocking rates or low shares of permanent pasture - request higher compensation payments than less intensive farms.
Keywords: 330; Naturschutz; Anreiz; Grasland; Diskrete Entscheidung; Schleswig-Holstein